1987
DOI: 10.1002/fut.3990070509
|View full text |Cite
|
Sign up to set email alerts
|

The effects of USDA crop announcements on commodity prices

Abstract: ecent studies on spot (stock, bonds, commodities) as well as on futures R markets have stirred academic interest on the effect of the economic impact of public announcements on prices. Scheduled releases of economic information (earnings, dividends, inflation, money supply, CPI, etc.) as well as non-scheduled announcements (tender offers, investment proposals, new patents and discoveries, etc.), were analyzed to determine whether prices reflected this information before it was released. These semi-strong marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…One is a constant mean return (CMR) model that measures abnormal returns as prediction errors from some benchmark model of normal returns. Examples cited earlier that have used the CMR model include Milonas (1987), Schroeder, Blair, and Mintert (1990), Mann andDowen (1997), andMcKenzie andThomsen (2001). A second approach involves regression methods with abnormal returns being estimated as coefficients of dummy variables that correspond to event days.…”
Section: Event Study Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…One is a constant mean return (CMR) model that measures abnormal returns as prediction errors from some benchmark model of normal returns. Examples cited earlier that have used the CMR model include Milonas (1987), Schroeder, Blair, and Mintert (1990), Mann andDowen (1997), andMcKenzie andThomsen (2001). A second approach involves regression methods with abnormal returns being estimated as coefficients of dummy variables that correspond to event days.…”
Section: Event Study Methodsmentioning
confidence: 98%
“…Milonas (1987), Schroeder, Blair, and Mintert (1990), Mann andDowen (1997), andMcKenzie andThomsen (2001) all use an 8-day normal period.…”
Section: Event Study Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the authors found that the impact of August, September, and October USDA harvest forecast releases were stronger than the forecasts announced in other months. Milonas () conducted a similar analysis with grain cash prices and the results pointed to a significant price adjustment after USDA report announcements.…”
Section: Previous Studiesmentioning
confidence: 97%
“…Two methods have been developed in the existing literature to calculate the normal return of commodity futures that serves as the benchmark, and both are adopted in the following analysis. First, following the mean return model by Milonas () and McKenzie, Thomsen and Dixon (), we use the average return over a length of time (from 30 trading days to 11 trading days before the event, which is in total 20 trading days) to determine what would otherwise be the normal return if the event had not occurred. The abnormal rate of return was calculated as the real return minus the normal return.…”
Section: Evidence Based On a Negative Shock To The Housing Marketmentioning
confidence: 99%